Appearance of Presumptions and Fictions in Tax Law// In Honorem Flavius Antoniu Baias: aparenţa în drept/ vol. coord. de: AdrianaAlmăşan, Ioana Vârsta, Cristina Elisabeta Zamşa. – Bucureşti - Babin, Igor (Editura Hamangiu, 2021)
The appearance of presumptions and fictions in law is associated with such property as formal certainty. For tax law, formal certainty is of particular importance. This is due to the fact that tax law is a public branch of law, which is characterized by complexity and dynamism, regulates highly politicized and conflicting relations regarding the financial support of public entities. Presumptions and fictions as a means of legal technique help to achieve certainty in tax law in cases where this cannot be achieved by other means of legal regulation.
Keywords: appearance in law, presumption, fiction, tax law, formal certainty of law